Marine Waste Reduction in the European Union: The Potential of Bioplastic Policy - Rahmat, Rhin Khairina; Atiya Nahda Fadilla; Izzatinnisa (Journal of World Trade Studies, 2024)
The accumulation of marine plastic waste represents a significant global environmental pollution issue. The European Union is a regional organisation that has implemented a marine plastic waste management strategy. This is due to the amount of waste on European beaches, which is dominated by about 50% of single-use plastics. The policy implemented by the European Union is to pay attention to the use of recyclable plastics including plastic processing strategies through the EU Plastic Strategy in 2018. Thus, this research aims to explain the EU's opportunity to implement bioplastics through single-use plastic policies that can reduce marine plastic waste. This research will be explained through analysis of the diffusion of innovation theory from Everett M. Rogers. Based on the implementation, the European Union can be a benchmark in plastic waste management to achieve a balance of sustainable development in the economic, environmental and social sectors. This is because the European Union has qualified policy development through the Single Use Plastic policy and the EU Policy Framework of Biobased, Biodegradable and Compostable Plastics.